From E-Government to Digital Government: SmartASN as a Sustainable Digital Innovation in Indonesia’s Public Sector (Public Accounting and Sustainability, 2025)
Research aims: The SmartASN was launched as a digital innovation in Indonesia’s public sector to facilitate the transition from e-government to digital government. This current study examines this integration process guided by the Digital Government Policy Framework proposed by the Organization for Economic Cooperation and Development. Design/Methodology/Approach: This study employs a qualitative method, analysing secondary data from official reports, journals, and mass media using the interactive model and NVivo 12 Plus software. Research findings: The study found six characteristics of the SmartASN helping this transition process: (1) Digital-by-design—using modern, interactive interfaces optimised for user accessibility across platforms; (2) Data-driven—using integrated data from multiple government agencies for personalized and efficient service delivery; (3) Government as a platform—providing a centralized, accessible system for delivering public services; (4) Open-by-default—ensuring transparency and trust through accessible and accountable information sharing; (5) User-driven—offering tailored, user-centric services based on preferences and feedback for continuous improvement; and (6) Proactive—anticipating user needs and enhancing efficiency through advanced technologies. Theoretical contribution/Originality: These findings contribute to understanding digital innovation in public sector governance, demonstrating how SmartASN aligns with global digital government principles and the importance of user-centred design and transparency in public sustainability. Practitioner/Policy implication: Policymakers can use these findings to use digital tools to enhance citizen engagement and service delivery.